Associação entre saúde bucal e nível de atividade inflamatória em pacientes com doença renal crônica submetidos à hemodiálise - Sousa, Luciana Abreu (2020)
Background: End-stage renal disease (ESRD) is associated with high levels of inflammation. Higher inflammation levels in hemodialysis (HD) patients increase mortality and decrease quality of life. Poor oral health can be an additional determinant of inflammation. Aim: To verify the association of dental disease and oral hygiene habits with inflammatory levels among ESRD patients submitted to regular HD. Methods: We studied 147 ESRD patients undergoing HD at a single treatment center. Oral examination of the participants was performed by a dentist and enabled the identification of decayed, missing and filled teeth. A questionnaire was applied containing questions about the use of tobacco, prostheses, the presence of teeth grinding and xerostomia. Oral hygiene habits were also covered by the questionnaire: use of toothbrushes, toothpaste, dental floss and the number of tooth brushings per day. High-sensitivity C-reactive protein (hs-CRP) was measured in order to estimate the inflammatory level among patients. Results: In the bivariate analysis, there was positive correlation between the number of filled teeth and hs-CRP (r=0.168; p=0.041) and negative correlation between the number of daily tooth brushings and hs-CRP (r=-0.165; p=0.045). hs-CRP was higher among patients without the use of dental floss compared to those with the habit of dental flossing (mean 11.6 mg/dl versus 4.6 mg/dl; p=0.043). In the multivariate analysis, the number of filled teeth and the habit of dental flossing were independent predictors of higher hs-CRP levels. Conclusion: Underuse of dental floss and high number of filled teeth was associated with higher inflammation level, as assessed by hs-CRP levels, in ESRD patients submitted to HD